Factors affecting birth weights of the Boran cattle in Tanzania - Mpiri, D.B.; Mpiri, M.T; Robison, O.W. (1987)
Birth weights of 1,030 Boran calves born between 1961 and 1979 at Malya Livestock Research Center in Tanzania were analysed to obtain means and study factors affecting this trait over the years under study and to estimate correction factors for effect of season and sex of calf. Also determined were heritability estimates from sire and dam components of variance. Last squares mean birth weights for Period I (1963-1969) and Period II (1970-1979) were 26.0± .5 and 25.4±7 respectively. Heritability estimates used on paternal half sibs were 0.33±0.12 and 0.18± 0.13, for periods I and II respectively. Year, season, sire, dam and sex effects were highly significant (P